Elevated cerebrospinal fluid protein levels associated with poor short-term outcomes after spinal cord stimulation in patients with disorders of consciousness - He, Qiheng; Li, Tianfei; Xiong, Ying; Xia, Xiaoyu; Dang, Yuanyuan; Chen, Xueling; Geng, Xiaoli; He, Jianghong; Yang, Yi; Zhao, Jizong (Frontiers in Aging Neuroscience, 2022)
Background Spinal cord stimulation (SCS) is a promising treatment for patients with disorders of consciousness (DoC); however, the laboratory examinations and different electrodes that are associated with postoperative outcomes are unclear. The study aims to study the association between the change in postoperative cerebrospinal fluid (CSF) protein level and improvement in consciousness after SCS in DoC patients and to explore whether different electrodes were associated with elevated CSF protein levels. Methods A total of 66 DoC patients who received SCS treatment from December 2019 to December 2021 were retrospectively analyzed. Patients were grouped according to their elevated CSF protein level. The clinical characteristics of the patients and SCS stimulation parameters were compared. Results We found that more DoC patients had elevated CSF protein levels among those receiving SCS treatment with permanent electrodes than temporary percutaneous electrodes (P = 0.001), and elevated CSF protein levels were significantly associated with a reduced sagittal diameter (P = 0.044). In DoC patients receiving SCS treatment, we found that elevated CSF protein levels (P=0.022) and preoperative diagnosis (P = 0.003) were significantly associated with poor outcomes at 3 months. Logistic regression analysis showed that elevated CSF protein levels were significantly associated with poor outcomes (OR 1.008, 95% CI 1.001-1.016, P=0.032). Conclusions The results suggest that reducing the effect of electrode pads on anatomical changes may help improve the outcomes of DoC patients receiving SCS treatment. CSF protein levels could be a potential biomarker in DoC patients receiving SCS treatment.